Efektifitas Pembelajaran Bahasa Arab 0 (nol) sks dalam membentuk Bi’ah al-‘Arabiyah pada Prodi PAI STIT Raden Wijaya - Musta’in (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Arabic subjects are very important to develop the ability to communicate. By learning Arabic, students can understand the conversation and reading in Arabic well. Formal Arabic Studies in Madrasahs are the main means for students to master Arabic. This study aims to: 1) Know the efforts of STI Pati Raden Wijaya Prodi in shaping Arabic environment on Prodi PIT STIT Raden Wijaya. 2) Knowing the supporting factors in shaping Arabic environment on PAI STIT Raden Wijaya Prodi. 3) Knowing the obstacles faced by Prodi PIT STIT Raden Wijaya in shaping Arabic environment at Prodi PIT STIT Raden Wijaya. This study uses oriented approach (paradigm) Descriptive-Qualitative, While the type of research is using case studies (Santoso, 2005). In this study the researchers themselves or with the help of others are the main data collectors. This research was conducted at Tarbiyah High School of Raden Wijaya Kota Mojokerto, on Islamic Religious Education Study Program. In this study, the primary data obtained by researchers is: the results of interviews with the Chairman of the Study Program of Islamic Education and Students Semester I (One). In this study used in analyzing data that has been obtained is by descriptive (non statistical) descriptive that is explorative. The conclusions of this research are: 1) Effort-uaha done Prodi in making effective learning arab language in Prodi PIT STIT Raden Wijaya are: a. He held yaum al-'araby twice a week on Friday. b. It was called shabah al-lughah a week twice before ta'lim afkar al-islamy began. c. The existence of study club on each mabna. 2) Factors that become supporters in forming bi'ah al-'arabiyah are: a. Attachment of mufradat in strategic places. b. Make plaques that are written / spoken in Arabic to make it easier to remember. c. Songs in foreign languages (Arabic and English) to increase students' insight in developing the language. 3) The constraints faced in creating bi'ah al-'arabiyah namely: a. Ability and basic students are different. b. There is no class classification that suits the ability of each student. c. Lack of facilities / facilities and infrastructure. d. Competence musyrif / ah who are not all able to speak. e. The curriculum and materials that are presented have not been neatly arranged. f. The absence of a strict iqob for students who do not communicate arabic language everyday.